Major determinants of survival and length of stay in the neonatal intensive care unit of newborns from women with premature preterm rupture of membranes. (18th August 2017) - Kurek Eken, Meryem; Tüten, Abdülhamit; Özkaya, Enis; Karatekin, Güner; Karateke, Ateş
Abstract: Objective : To assess the predictors of outcome in terms of length of stay in the neonatal intensive care unit (NICU) and survival of neonates from women with preterm premature rupture of membranes (PPROM). Methods : A population-based retrospective study including 331 singleton pregnant women with PPROM at 24–34 gestational weeks between January 2013 and December 2015 was conducted. Gestational age at delivery, birth weight, route of delivery, newborn gender, maternal age, oligohydramnios, premature retinopathy (ROP), necrotising enterocolitis (NEC), sepsis, fetal growth retardation (FGR), intracranial hemorrhagia (ICH), bronchopulmonary dysplasia (BPD), respiratory distress syndrome (RDS), primary pulmonary hypertension (PPH), congenital cardiac disease (CCD), patent ductus arteriosus (PDA), use of cortisol (betamethasone) and maternal complications including gestational diabetes, preeclampsia and chorioamnionitis were used to predict neonatal outcomes in terms of length of stay in the NICU and survival. Results : In linear regression analyses, birth weight, ROP, CCD, BPD, PDA, NEC and preeclampsia were significant confounders for length of stay in the NICU. Among them, birth weight was the most powerful confounder for prolongation of the NICU stay ( t : −6.43; p  < 0.001). In multivariate logistic regression analyses, birth weight, PDA, ROP and PPH were significantly correlated with neonatal survival. PPH was the most powerful confounder in neonatal survival ( β : 7.22; p  = 0.005). Conclusion : Prematurity-related complications are the most important problems for which precautions should be taken. Therefore, premature deliveries should be avoided to prevent infection and to prolong the latent period in cases of PPROM in order to decrease prematurity-related outcomes.